Suicide and Microglia: Recent Findings and Future Perspectives Based on Human Studies - Suzuki, Hisaomi; Ohgidani, Masahiro; Kuwano, Nobuki; Chrétien, Fabrice; Lorin de la Grandmaison, Geoffroy; Onaya, Mitsumoto; Tominaga, Itaru; Setoyama, Daiki; Kang, Dongchon; Mimura, Masaru; Kanba, Shigenobu; Kato, Takahiro A. (Frontiers in Cellular Neuroscience, 2019)
Suicide is one of the most disastrous outcomes for psychiatric disorders. Recent advances in biological psychiatry have suggested a positive relationship between some specific brain abnormalities and specific symptoms in psychiatric disorders whose organic bases were previously completely unknown. Microglia, immune cells in the brain, are regarded to play crucial roles in brain inflammation by releasing inflammatory mediators and are suggested to contribute to various psychiatric disorders such as depression and schizophrenia. Recently, activated microglia have been suggested to be one of the possible contributing cells to suicide and suicidal behaviors via various mechanisms especially including the tryptophan-kynurenine pathway. Animal model research focusing on psychiatric disorders has a long history, however, there are only limited animal models that can properly express psychiatric symptoms. In particular, to our knowledge, animal models of human suicidal behaviors have not been established. Suicide is believed to be limited to humans, therefore human subjects should be the targets of research despite various ethical and technical limitations. From this perspective, we introduce human biological studies focusing on suicide and microglia. We first present neuropathological studies using the human postmortem brain of suicide victims. Second, we show recent findings based on positron emission tomography (PET) imaging and peripheral blood biomarker analysis on living subjects with suicidal ideation and/or suicide-related behaviors especially focusing on the tryptophan-kynurenine pathway. Finally, we propose future perspectives and tasks to clarify the role of microglia in suicide using multi-dimensional analytical methods focusing on human subjects with suicidal ideation, suicide-related behaviors and suicide victims.